EVALUATION OF THE CIPP MODEL IN THE IMPLEMENTATION OF KTSP PHYSICAL EDUCATION LEARNING - maulana, syahril (Universitas Syiah Kuala, 2024)
The implementation of KTSP at Aceh Besar District Public High Schools needs to be evaluated in order to improve and strengthen the quality of student learning. Teachers as educators are expected to be able to develop learning models. The aim of this research is to determine the Context, Input, Process and product in the Implementation of KTSP physical education learning at State High Schools in Aceh Besar Regency. Type of evaluation research with a qualitative approach. Research subjects of Aceh Besar District High School. The population and sample in this study were 3 school principals, 3 physical education teachers and 39 students, while data collection used observation, interview and documentation instruments. Data analysis uses data reduction, display and verification. The results of research on the application of the Cipp model in the implementation of KTSP physical education learning at State High Schools in Aceh Besar Regency have gone well (systematic, planned, regular and continuous).Keywords: Evaluation, CIPP Model, Physical Education Learning